2007
DOI: 10.1063/1.2714650
|View full text |Cite
|
Sign up to set email alerts
|

Application of the three omega method for the thermal conductivity measurement of polyaniline

Abstract: The three omega method has proven to provide accurate and reliable measurements of thermal conductivity of thin films and other materials. However, if the films are soft and conductive, conventional methodologies to prepare samples for the measurement technique are challenging and often unachievable. Various modifications to the sample preparation to employ this technique for soft conducting films are reported in this paper including the use of shadow masks for metal heater deposition and a process for prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Thermal transport properties of the composite membranes PSN and PRSN membranes, the incorporation of ARS and NRS particles in the PANI matrix revealed an obvious increase in thermal conductivity. For example, PANI exhibited thermal conductivity (k, W/(m·K)) of 0.0933 [38], which was lower than that of PSN and PRNS membranes. It should be noted that the k value of the PSM membrane containing 3 wt% of AMS particles was clearly lower than those of PSN3, PRSN3, and PANI membranes.…”
Section: Thermal Transport Propertiesmentioning
confidence: 92%
“…Thermal transport properties of the composite membranes PSN and PRSN membranes, the incorporation of ARS and NRS particles in the PANI matrix revealed an obvious increase in thermal conductivity. For example, PANI exhibited thermal conductivity (k, W/(m·K)) of 0.0933 [38], which was lower than that of PSN and PRNS membranes. It should be noted that the k value of the PSM membrane containing 3 wt% of AMS particles was clearly lower than those of PSN3, PRSN3, and PANI membranes.…”
Section: Thermal Transport Propertiesmentioning
confidence: 92%
“…It is found that the thermal conductivity of all studied samples decreases rather linearly from room temperature to 100 K, as expected for a conducting polymer or a glass (amorphous). 33 Below 70 K, j increases rapidly and develops a peak at $25 K with a value of about 0.5-0.8 W m À1 K À1 , below which it falls abruptly as T decreases. The peak, observed commonly in semi-crystalline and crystalline organic materials, 34 not in previously known conducting polymers, is interpreted as that of a semi-crystal, i.e., glassy material in a crystal form, and it is a potential candidate for good thermoelectrics (see supplementary material 14 ).…”
mentioning
confidence: 97%
“…14 At 300 K, j is larger (0.5-0.7 W m À1 K À1 ) than that of thin Pani-CSA film (0.15 W m À1 K À1 ), 25 but comparable to those of inorganic thermoelectrics (0.6-1.5 W m À1 K À1 ) 7 and Pani-CSA thick film (0.6 W m À1 K À1 ). 25,33 These low thermal conductivities are typical of amorphous materials. The smallest possible thermal conductivity in a solid as predicted by Slack in 1977 is when the mean-free path of the phonons is equal to the smallest distance in the solid.…”
mentioning
confidence: 98%
“…The thermal conductivities of PANI and PA also increase below T g with increasing temperature because of enhanced specific heat. 22,23 Figure 3 presents the variation of j pn and j p PANI for configurations 1 and 4, described in the supplementary material, 13 at different temperatures. j p PANI increases with temperature up to 300 K and then slightly decreases close to T g (493 K), suggesting an increase in phonon scattering from emerging defects in form of voids.…”
Section: Figmentioning
confidence: 99%